The world of Bernini, 1598-1680 - Wallace, Robert 1919-; Time-Life Books ((Nederland) B.V. Time-Life Books, 1970)
An account of the life, work and times of Bernini, great sculptor of 17th century Italy.
Art and faith -- The pope's favorite -- Caravaggio: turbulent genius -- The fountains of Rome -- Sculptures that speak -- Saints and angels -- Pilgrimage to St. Peter's -- Chronology of artists.
Includes bibliographical references (page 185) and index.
Keywords: Bernini, Gian Lorenzo -- 1598-1680.